Seroprevalence of HIV, hepatitis B virus, and HCV among injection drug users in Connecticut: understanding infection and coinfection risks in a nonurban population. - Akselrod, Hana; Grau, Lauretta E; Barbour, Russell; Heimer, Robert (American journal of public health, 2014)
We examined HIV, hepatitis B virus (HBV), and HCV seroprevalence in an interim analysis and the potential risk factors associated with these infections among injection drug users (IDUs) residing in nonurban communities of southwestern Connecticut.
Keywords: Adult; Coinfection; Connecticut; Depression; Drug Overdose; Female; Hepatitis B; Hepatitis C; HIV Infections; Humans; Male; Middle Aged; Risk Factors; Seroepidemiologic Studies; Socioeconomic Factors; Substance Abuse, Intravenous; Time Factors